The history of matrix metalloproteinases: milestones, myths, and misperceptions - Iyer, Rugmani Padmanabhan (American Physiological Society, 2012)
Since the discovery of tadpole collagenase in 1962, the matrix metalloproteinase (MMP) family has emerged as a significant proteinase group with recognized effects on the cardiovascular system. Over the last 40 years, many milestones have been achieved, from the identification of the first MMP, to the generation of the first MMP cDNA clone and null mouse, to the clinical approval of the first MMP inhibitor. Over the years, a few myths and misunderstandings have interwoven into the truths. In this review, we will discuss the major milestones of MMP research, as well as review the misinterpretations and misperceptions that have evolved. Clarifying the confusions and dispelling the myths will both provide a better understanding of MMP properties and functions and focus the cardiovascular field on the outstanding research questions that need to be addressed.